Estimating a runner's stride length and frequency from a race video by using ground stitching - Yagi, K.; Hasegawa, K.; Sugiura, Y.; Saito, H. (ISBS Proceedings Archive (Michigan), 2018)
This study estimated stride length and frequency of runners in a 100 m race video. One method for measuring stride length and frequency is using infrared sensors. However, this method is not applicable to real races since numerous markers with infrared-reflective material must be attached to the runner`s entire body. Therefore, we proposed a method using a race video. We generated a panoramic image of the 100 m track to estimate the distance of each frame from the start line. We detected the positions of the runner`s steps from the movement of the leg joints. We projected every step to the overview image of the 100 m track. In the experiment, we applied our method to the video of an IAAF World Championship Track and Field 100 m race and obtained data from Usain Bolt. As a result, we can automatically estimate stride length and frequency of real races.